التكوين التأريخي للشخصية العراقية القديمة (Journal of the College of Basic Education, 2022)
History witnessed across its long marsh new civilizations appear and others ended. Each one owned its factors of development and reasons of ended. History witnessed a long period of Mesopotamia ruled by different rulers who differed from each other's by race or culture from the Samarian until the Islamic era. History recorded the countries and civilizations that thrive then faded، dead and the cultural heritage of haplites، traditions and arts that transfers to other cultures. The compositions of the cultural mentality owned by the people of Mesopotamia since its firth growth with changeable environmental specifications. The historical evidence shows that they interact with their environment and adopted it، the humanitarian civilization takes developing and branches until our era where human history since the first time of him on earth across the longtime of life takes many circles of developing.